Can the Risk Factors Predicting Surgical Treatment be Determined in Patients with Tubo-Ovarian Abscess? - Tayfun Vural; Burak Bayraktar; Suna Yildirim Karaca; Emir Gurbuz; Mehmet Ozeren; Cuneyt Eftal Taner (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: In this study, we aimed to determine the risk factors in predicting the need for surgical treatment due to medical treatment failure in patients with tubo-ovarian abscess.